Assessment of socioeconomic and ecological impacts on integrated rice cultivation in Africa: a systematic review and meta-analysis - Emmy Goh Ling Ling; Elliott Ronald Dossou-Yovo; Rodrigue Yossa (International Journal of Agricultural Sustainability)
Integrated rice-fish (RF) is seen as a valuable system to increase food production and farmers’ income in Africa. To date, no research has been conducted to comparatively assess integrated RF, rice, and fish monoculture systems in Africa. This study aimed to evaluate the agronomic and economic performances and identify constraints and enabling conditions for large-scale adoption of RF systems in Africa. Systematic review and meta-analysis were performed using papers collected from January 1999 to December 2023 and 30 pair-observations. The results showed a significant effect on FGR (+6%) in integrated RF compared to fish monoculture. The production cost increased by 300 USD/ha in integrated RF, but the gross revenue increased by more than 600 USD/ha resulting in an increase in net income by 300 USD/ha compared to rice monoculture. NUE, soil properties, and control of weeds, pests, and diseases were enhanced in the integrated RF compared to rice monoculture. Land ownership, water supply unreliability, access to fish feed and fingerlings, and lack of funding were the major factors limiting integrated RF adoption by farmers. Due to the limited data identified in this study, more field observations and long-term monitoring are necessary on land suitability and management practices for integrated RF.